2017
DOI: 10.1016/j.pedneo.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress in parents of children with refractory epilepsy before and after vagus nerve stimulation implantation

Abstract: VNS is an advisable choice to treat refractory epilepsy. Our study showed that 12 months or more after VNS implantation, seizure frequency and parenting stress typically decreased. However, in some special cases the parenting stress may increase, and external help may be required to support these patients and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…25 Li et al enrolled 30 patients and found seizure reduction rate of 42.6%, and 15 patients (50%) had S50% seizure reduction rate, with one seizurefree patient (3.3%). 26 Although the studies of Tsai et al and Li et al aimed to investigate the impact of VNS on neuropsychological outcome in children with RE and parenting stress, their seizure reduction outcomes are consistent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…25 Li et al enrolled 30 patients and found seizure reduction rate of 42.6%, and 15 patients (50%) had S50% seizure reduction rate, with one seizurefree patient (3.3%). 26 Although the studies of Tsai et al and Li et al aimed to investigate the impact of VNS on neuropsychological outcome in children with RE and parenting stress, their seizure reduction outcomes are consistent with our study.…”
Section: Discussionsupporting
confidence: 90%
“…The impact of VNS on QALY was assessed taking into account the following: the difference in the average utility score of QoL between the post-VNS period and the 6-months pre-VNS period; age; gender; and life expectancy in the entire VNS population [ 106 ]. VNS improved different health-related quality of life (HRQOL) domains—mainly cognitive, psychological, and social [ 92 , 107 , 108 , 109 ]—but it also improved memory, mood, behavior, alertness, achievement, and verbal skills [ 97 , 98 , 110 , 111 , 112 , 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 Meta-analysis results of effect size for corpus callosotomy. P = 0.000, I 2 = 83.8% satisfaction with VNS in generalized epilepsy [26]. Therefore, in selecting an appropriate initial surgical procedure for each child, individual family priorities with regard to most functionally limiting seizure type and expected functional outcome must be taken into account.…”
Section: Discussionmentioning
confidence: 99%